Precursors of literacy delay among children at genetic risk of dyslexia. - Gallagher, A; Frith, U; Snowling, M (2000)
This paper reports the literacy skills of 63 children selected as being at genetic risk of dyslexia compared with 34 children from families reporting no history of reading impairment. Fifty-seven per cent of the at-risk group were delayed in literacy development at 6 years compared with only 12% of controls. The "unimpaired" at-risk group were not statistically different from controls on most cognitive and language measures at 45 months, whereas the literacy-delayed group showed significantly slower speech and language development, although they did not differ from controls in nonverbal ability. Letter knowledge at 45 months was the strongest predictor of literacy level at 6 years. In addition, early speech and language skills predicted individual differences in literacy outcome and genetic risk accounted for unique variance over and above these other factors. The results are discussed in terms of an interactive developmental model in which semantic and phonological skills support early reading acquisition.